1978
DOI: 10.1007/bf01915370
|View full text |Cite
|
Sign up to set email alerts
|

Plasma triiodothyronine, thyroxine and thyrotrophin levels in germfree rats

Abstract: Plasma T3, T4 and TSH levels in developing germfree rats were high, low and normal as compared with those in conventional counterparts. The high T3/T4 ratio in germfree rat plasma was lowered by cholestyramine feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Plasma tetraiodothyronine (T4) and triiodothyronine (T3) concentrations were determined in duplicate using an ELISA method (Immunodiagnostics Enzymun Tests T4 and T3; Boehringer Mannheim, Meylan, France). These Enzymun kits, originally designed for use with human plasma, have been used previously (Nugon-Baudon et al 1990a, b); data obtained for rats using these kits are consistent with those reported by other authors using different methods (Ukai & Mitsuma, 1977;Jordan et al 1980;Vermorel et al 1986Vermorel et al , 1988.…”
Section: Hormone Assayssupporting
confidence: 78%
“…Plasma tetraiodothyronine (T4) and triiodothyronine (T3) concentrations were determined in duplicate using an ELISA method (Immunodiagnostics Enzymun Tests T4 and T3; Boehringer Mannheim, Meylan, France). These Enzymun kits, originally designed for use with human plasma, have been used previously (Nugon-Baudon et al 1990a, b); data obtained for rats using these kits are consistent with those reported by other authors using different methods (Ukai & Mitsuma, 1977;Jordan et al 1980;Vermorel et al 1986Vermorel et al , 1988.…”
Section: Hormone Assayssupporting
confidence: 78%
“…This is the first report to study the effect of probiotics on the rate of thyroid hormones in Holstein's calves. The same results have been recorded in the blood plasma in developing germ-free rats when compared to conventional rats [10]. Raise in the rate of hepatic conversion of thyroxin into Triiodothyronine in the liver of the conventional rats and decreased from the bile salts [11].…”
Section: Resultssupporting
confidence: 55%
“…Recently, the alteration of the hormonal state of the host by intestinal microflora has been recognized (14,21,22). High endocrine response in formula-fed infants has also been reported by Lucas et al (15).…”
Section: Resultsmentioning
confidence: 90%